High prevalence of vitamin D deficiency and reduced bone mineral density in multiple sclerosis - Ozgocmen, S; Bulut, S; Ilhan, N; Gulkesen, A; Ardicoglu, O (Elsevier Science Inc, 2003)
[Abstract Not Available]
1ST Joint meeting of the International-Bone-and-Mineral-Society/Japanese-Society-for-Bone-and-Mineral-Research -- JUN 03-07, 2003 -- OSAKA, JAPAN